2018
DOI: 10.1111/jnp.12174
|View full text |Cite
|
Sign up to set email alerts
|

The role of hippocampus in the retrieval of autobiographical memories in patients with amnestic Mild Cognitive Impairment due to Alzheimer's disease

Abstract: The role of the hippocampus and neocortical areas in the retrieval of past memories in pre‐dementia Alzheimer's disease (AD) patients was investigated. The aim was to assess whether the hippocampus has a temporary role in memory trace formation, according to the Cortical Reallocation Theory (CRT), or whether it continuously updates and enriches memories, according to the Multiple Trace Theory. According to the former theory, hippocampal damage should affect more recent memories, whereas the association cortex … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 93 publications
1
19
0
Order By: Relevance
“…Moreover, the hippocampus is critical for initial encoding of events and their embedding in emotional context (3,19,20,95), and the anterior temporal lobe is likely to be important for the semantic integration of autobiographical events (96). The integrity (or partial integrity) of these brain areas might plausibly support a tendency to re-live past autobiographical events, in line with previous evidence in neurodegenerative syndromes (97)(98)(99).…”
Section: Discussionsupporting
confidence: 75%
“…Moreover, the hippocampus is critical for initial encoding of events and their embedding in emotional context (3,19,20,95), and the anterior temporal lobe is likely to be important for the semantic integration of autobiographical events (96). The integrity (or partial integrity) of these brain areas might plausibly support a tendency to re-live past autobiographical events, in line with previous evidence in neurodegenerative syndromes (97)(98)(99).…”
Section: Discussionsupporting
confidence: 75%
“…Across all 40 patients, the correlation with medial temporal volume was r = .42, p < .05; and in 14 patients whose primary pathology was in the medial temporal lobes (or 'hippocampal complex', see p. 880 of that paper), it was only r = .28 and not significant. Other investigators have also found that the degree of autobiographical episodic impairment is not closely correlated with the severity of hippocampal atrophy (Serra et al, 2018;Tomadesso et al, 2015). In a recent review, Sekeres, Winocur, and Moscovitch (2018) concluded the same, but postulated specialisation in subfields along the long axis of the hippocampi.…”
Section: Theories Of Ra and The Temporal Gradientmentioning
confidence: 95%
“…Various neuroimaging studies have demonstrated abnormal structure and function of the hippocampus in patients with AD and MCI. β-Amyloid abnormalities and tau pathology in the preclinical stages of AD initially appear in the hippocampus (Braak and Braak, 1991; Hanseeuw et al, 2016; Serra et al, 2018). Longitudinal studies have shown significant volume loss in the hippocampus during the progression of AD, and there is a direct relationship with cognitive decline (Everitt and Dunn, 2013; Joko et al, 2016).…”
Section: Introductionmentioning
confidence: 99%